Antiphospholipid syndrome associated with non-infective mitral valve endocarditis: a case report (Journal of Health Sciences, 2014)
We present a rare case of antiphospholipid syndrome associated with non-infectious thrombotic endocarditis of the mitral valve. The patient was admitted to hospital for examination because of skin lesions manifested through a discoid skin rash. During the hospitalization antiphospholipid syndrome was diagnosed along with ultrasound verification of vegetations on the mitral valve, including both leaflets, with moderate to severe mitral regurgitation. Adequate and opportunely introduced therapy led to regression of all symptoms, including endocarditis of the mitral valve on checkup ultrasound verifications, with a prevention of arterial and/or venous thrombosis in patient's future.